PENINGKATAN KAPASITAS PENGURUS DALAM PENGELOLAAN ADMINISTRASI PONDOK PESANTREN API SYUBBANUL WATHON METESEH - Siswanto Siswanto; Sekar Meika Chandra (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2021)
This service aims to increase the board's capacity in managing the administration of the cottage. Increasing the degree of administrators in the administration of Islamic boarding schools is very necessary so that administrative or administrative activities of Islamic boarding schools run well and smoothly. To support organizational goals, an admin is closely related to correspondence, recording, compiling, entering data, bookkeeping, setting the plan, and other technical matters. API SW is an Islamic boarding school whose students are students; the students' data must be complete and should be superior to other boarding schools. This service uses a PAR (Participation Action Research) approach. The method applied is through archiving management guidance activities to all administrators, providing excel training, and contributing to the cottage office. And the implementation of the service, the board of the API SW Islamic boarding school can arrange the administration well.